Lidocaine Clearance as Pharmacokinetic Parameter of Metabolic Hepatic Activity in Patients with Impaired Liver - Jovanović, Marija; Kovačević, Milena; Vezmar Kovačević, Sandra; Palibrk, Ivan; Bjelanović, Jasna; Miljković, Branislava; Vučićević, Katarina (Journal of Medical Biochemistry, 2022)
Background The study aimed to estimate lidocaine (LID) pharmacokinetic parameter values in patients with impaired liver function, and to assess change in parameters related to the surgical intervention. Methods Patients with impaired liver function were subject to the test prior to, 3 and 7 days after the intervention. LID was administered in single i.v. dose of 1 mg/kg. Blood samples were collected at 15, 30 and 90 minutes after drug administration. Non-compartmental analysis was applied for calculating the pharmacokinetic parameters. Results The study included 17 patients with the diagnosis of cirrhosis and 41 patients with liver tumor. In both groups of patients, the values of the coefficients of correlation show the best correlation between CL and Child-Pugh score (-0.693, p<0.005) over other pharmacokinetic parameters. The results indicate worsening hepatic function on 3rd day after operation in comparison to the values of LID CL prior to operation (mean LID CL for patients with Child-Pugh class A are 25.91 L/h, 41.59 L/h, respectively; while for B class are 16.89 L/h, 22.65 L/h, respectively). On day 7th, the values of LID CL (mean value for patients with Child-Pugh class A and B are 40.98 L/h and 21.46 L/h, respectively) are increased in comparison to 3rd day after. Conclusions LID pharmacokinetic parameters consequently changed according to the severity of liver impairment, assessed by Child-Pugh score. Values of LID CL and Vd coupled with standard biochemical parameters may be used in obtaining the complete picture of hepatic status of patients.